Service Quality Perceptions of Customers about Insurance Companies:An Empirical Study - Gautam, Vikas (Indian Journal of Marketing, 2011)
After the implementation of government policies on globalization and liberalization, the consumers have become more critical of the quality of service. Consumers are now very much aware of the alternatives available in relation to services and the provider organizations. Expectations of consumers are rising and the provider organizations should be aware of these expectations. The objective of the present study is to compare and analyze the service quality perceptions of customers about the public sector and private sector insurance companies. The study also seeks to find the relevant dimensions of the SERVQUAL/SERVPERF scale in insurance industry in the Indian context. A total of 210 respondents completed the field survey, and the survey was conducted in the Hyderabad city of Andhra Pradesh. The primary statistical techniques used in the study are Correlation analysis, Factor analysis and Multiple regression analysis. An attempt has been made here to quantitatively study the levels of the dimensions of service quality and its relation to customer service quality perceptions. Results of overall service quality perceptions show that public insurance companies are rated high as compared to private insurance sector companies. Exploratory factor analysis was used and five factors were extracted using the method of principal component analysis. The five factors extracted in case of public sector insurance company explained 78.34% of the variance; whereas five factors extracted in case of private sector insurance company explained 77.07% of the variance. The correlation analysis results show that all the five dimensions are highly relevant for service quality perceptions in insurance sector, as correlation coefficient ’r’ values for all the dimensions range from 0.945 to 0.973. Regression analysis with overall service quality perceptions as dependent variable, and five extracted factors as independent variables was run in SPSS 17.0. Regression results show that except tangibility dimension, beta coefficient values for other four dimensions of service quality namely; empathy, reliability, assurance, responsiveness are higher in case of public sector insurance companies. Statistically, beta coefficient values for reliability, assurance dimensions are higher in case of public sector life insurance companies as compared to private sector life insurance companies. Whereas only one dimension tangibility got statistically higher beta coefficient value for private sector life insurance companies. The present study was conducted under the null hypothesis that there is no significant difference in the service quality perceptions of public and private sector insurance companies. Results of t-test rejected the null hypothesis, led to the inference that there is significant difference in the service quality perceptions of public and private sector insurance companies. In all, the present study arrived at a conclusion that customers perceive better quality of service for public sector insurance companies as compared to private sector insurance companies.